Assessment of tsunami magnitude and implications for urban hazard planning in Greece - Dominey-Howes, D.T.M. (1998)
This paper describes the phenomenon of tsunamis within the European Seas and explains how tsunami research has developed during the last 40 years as a response to a large tsunami which occurred in the Aegean Sea region of Greece in 1956. The paper states that specific tsunami hazard maps have been established for particular coastal areas of Greece and that these maps and any associated disaster management plans have been developed as a tool to mitigate the effects of future tsunamis in the region. The author provides the results of new investigations of the effects of a past tsunami in Greece and shows that the magnitude of this event has been overestimated. The results imply that revisions of the urban hazard maps and associated disaster preparedness plans should be considered. - Reproduced
Keywords: Disasters - Greece; Natural disasters - Greece; Disasters